Posterior segmente intraocular inflammation : guidelines - Forrester, John V. (Kugler Publications, 1998)
Thi is the second educational publication of the international Ocular Inflammation Society wich deals with one the most important aspects of ofphthalmology - posterior segment intraocular inflamtionPSII, or as it is more commonly terned, posterior uveitis.